High-strength PET polyester material and preparation method thereof
By modifying glass fibers and combining them with PET resin, high-strength PET polyester materials were prepared, which solved the problems of poor mechanical properties and low heat resistance of existing PET materials, and achieved better in humid and heat environments Good stability and performance.
Patent Information
- Application Number
- CN202411767743.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-11
AI Technical Summary
The existing PET polyester materials have poor mechanical properties, high water absorption and low heat resistance, which limit their application in a variety of complex environments, especially in humid and hot environments, which will greatly reduce their stability and strength.
Modified glass fibers are prepared by silane coupling agent treatment and click chemical reactions, and fully mixed with PET resin, toughener and antioxidant, melting, extruding and Granulation to prepare high-strength PET polyester material.
The strength and humidity resistance of PET polyester materials are improved, so that they can show better stability and performance in a variety of complex environments, especially in humid and heat environments.
Smart Images

Figure CN119409997A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer materials, and in particular to a high-strength PET polyester material and a preparation method thereof. Background Art
[0002] Polyester is mainly made of dihydric or polyhydric alcohols and carboxylic acids through polycondensation reaction, and can be generally divided into two categories: unsaturated polyester and saturated polyester. Unsaturated polyester contains non-aromatic unsaturated bonds in its molecular structure, which can be induced to cross-link to form thermosetting polymer materials with a network (body) structure. Its leading product is polyester fiberglass reinforced plastics; saturated polyester does not contain non-aromatic unsaturated bonds in its molecular structure and is a linear thermoplastic polymer material.
[0003] The most widely used polyester material at present is polyethylene terephthalate (PET). When PET is used as an engineering plastic, it needs to be modified. The mechanical properties of pure PET resin without reinforcement or filling are not good. PET products used as engineering plastics are all modified by glass fiber or mineral filling. Adding fibers (such as glass fiber, carbon fiber, etc.) to polyester can greatly improve the mechanical properties of polyester, such as tensile strength. The impact strength of fiber-reinforced polyester composites will be further improved with the increase of polyester molecular weight, but since high molecular weight polyester is not conducive to the combination of resin and fiber, the compatibility of fiber and resin is not very good, so that the strength of polyester materials cannot be further improved. In addition, PET material itself has the defects of high water absorption and low heat resistance, which greatly limits its application in a variety of complex environments, especially in a hot and humid environment, there is a phenomenon of decreased stability and greatly reduced strength. Summary of the invention
[0004] In view of the problems existing in the prior art, the object of the present invention is to provide a high-strength PET polyester material and a preparation method thereof.
[0005] The purpose of the present invention is achieved by adopting the following technical solutions:
[0006] In a first aspect, the present invention provides a method for preparing a high-strength PET polyester material, comprising the following steps:
[0007] Step 1, preparing modified glass fiber:
[0008] The glass fiber is treated with a silane coupling agent KH-570 to obtain a surface double-bonded glass fiber; and then the surface double-bonded glass fiber is subjected to a click chemical reaction with a mercapto-polysiloxane to prepare a modified glass fiber;
[0009] Step 2, preparation of high-strength PET polyester material:
[0010] After drying, PET resin, toughening agent and antioxidant are added into a mixer, fully mixed, and then introduced into a twin-screw extruder. Then, the modified glass fiber is added into the extruder through a side feed port. After melting, extrusion and granulation, a high-strength PET polyester material is obtained.
[0011] Preferably, in step 1, the glass fiber is alkali-free glass fiber with a fineness of 1-20 μm and a length of 1-10 mm.
[0012] Preferably, in step 1, the method for preparing the surface double-bonded glass fiber comprises:
[0013] Firstly, silane coupling agent KH-570 is dissolved in ethanol solution, then added into glass fiber, and ultrasonic treatment is performed. After the treatment, the glass fiber is filtered, washed and dried to prepare the surface double-bonded glass fiber.
[0014] Preferably, in the preparation process of the surface double-bonded glass fiber, the mass fraction of the ethanol solution is 70%-80%, and the mass volume ratio of the glass fiber, the silane coupling agent and the ethanol solution is 1g:(0.2-0.4)g:(6-12)mL.
[0015] Preferably, during the preparation of the surface double-bonded glass fiber, the frequency of ultrasound is 25-35 kHz and the ultrasound time is 2-6 h.
[0016] Preferably, in step 1, the preparation method of mercapto polysiloxane comprises:
[0017] Take terminal hydroxyl polysiloxane, 4-mercaptobutyric acid and solvent chloroform, mix them, add 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 4-dimethylaminopyridine after stirring evenly, and stir them magnetically at room temperature for 16-32 hours. After the reaction is completed, remove the solvent under reduced pressure, and then wash and dry to obtain mercapto polysiloxane.
[0018] Preferably, in the preparation process of the mercapto polysiloxane, the terminal hydroxyl polysiloxane is a hydroxyl-terminated polydimethylsiloxane with a molecular weight of 1000-2000 and a hydroxyl content of 1.5wt%-3.5wt%.
[0019] Preferably, in the preparation process of the mercapto polysiloxane, the mass volume ratio of the terminal hydroxyl polysiloxane, 4-mercaptobutyric acid and chloroform is 10g:(5.4-7.2)g:(50-100)mL.
[0020] Preferably, in the preparation process of the mercapto polysiloxane, the mass ratio of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 4-dimethylaminopyridine and hydroxy-terminated polysiloxane is 2.1-3.6:0.6-1.2:10.
[0021] Preferably, in step 1, the preparation method of the click chemistry reaction comprises:
[0022] The mercapto polysiloxane and chloroform are mixed and stirred until uniform, and the surface double-bonded glass fiber and the photoinitiator are added, and then stirred under ultraviolet light. After the reaction is completed, the liquid is removed by suction, and the modified glass fiber is obtained after washing and drying.
[0023] Preferably, during the click chemistry reaction, the photoinitiator is benzoin dimethyl ether or benzoin diethyl ether, and the added amount is 0.6%-1.2% of the mass of the mercapto polysiloxane.
[0024] Preferably, during the click chemistry reaction, the intensity of ultraviolet light irradiation is 300-350 μW / cm 2 , the irradiation wavelength is 320-400nm, the stirring time is 1-2h, and the stirring speed is 100-200r / min.
[0025] Preferably, during the click chemistry reaction, the mass volume ratio of the surface double-bonded glass fiber, the mercapto-polysiloxane and the chloroform is 1 g:(1.3-2.6) g:(10-20) mL.
[0026] Preferably, in step 2, the PET resin is polyethylene terephthalate (PET) resin with a density of 1.36-1.40 g / cm 3 , the melt index is 6-10g / 10min (190℃ / 2.16kg).
[0027] Preferably, in step 2, the toughening agent is one or more combinations of Arkema AX8900, Arkema E920, and Arkema AC1820.
[0028] Preferably, in step 2, the antioxidant is one or more combinations of antioxidant 1098, antioxidant 1330, antioxidant 1790, and antioxidant 259.
[0029] Preferably, in step 2, the drying process is carried out in an oven at 100-120° C. for 4-8 hours.
[0030] Preferably, in step 2, the screw speed of the twin-screw extruder is 50-150 rpm, the aspect ratio L / D is 25-30:1, and the extrusion temperature is 240-290°C.
[0031] Preferably, in step 2, the extrusion temperature ranges include: zone 1: 240-260°C, zone 2: 240-260°C, zone 3: 250-290°C, zone 4: 250-290°C, zone 5: 250-290°C.
[0032] Preferably, in step 2, the mass ratio of PET resin, toughening agent, antioxidant and modified glass fiber is 80-90:2-5:1-3:10-30.
[0033] In a second aspect, the present invention provides a high-strength PET polyester material prepared using the above-mentioned preparation method.
[0034] The beneficial effects of the present invention are:
[0035] 1. The present invention discloses a novel PET polyester material, which is obtained by improving the traditional PET material and has not only high strength but also good moisture and heat resistance. The present invention improves the PET material mainly by modifying the glass fiber of its reinforcing material, so that the compatibility of the glass fiber and the resin is improved, and the mechanical properties and environmental adaptability of the PET material are also enhanced.
[0036] 2. The modification of glass fiber by the present invention is that the surface of the glass fiber is firstly activated by vinyl silane so that a large number of double bond groups are grafted onto the surface of the glass fiber, and then a thiol-modified polysiloxane is used to combine with the glass fiber to generate a click chemistry reaction to generate a large number of thioether (RSR) groups, thereby coating the surface of the glass fiber with polysiloxane groups to finally obtain modified glass fiber.
[0037] 3. Mercapto polysiloxane is prepared by using terminal hydroxyl polysiloxane and 4-mercaptobutyric acid as raw materials and undergoing catalytic esterification using an EDC·HCl / DMAP system. The mercapto polysiloxane molecules obtained contain a large number of mercapto groups. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] The present invention is further described using the accompanying drawings, but the embodiments in the accompanying drawings do not constitute any limitation to the present invention. A person skilled in the art can obtain other drawings based on the following drawings without creative work.
[0039] Figure 1 is a scanning electron microscope (SEM) schematic diagram of the modified glass fiber prepared in Example 1 of the present invention;
[0040] Figure 2 It is a scanning electron microscope (SEM) schematic diagram of the PET polyester material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0041] The technical solution of the present invention is described below through specific examples. It should be understood that the one or more method steps mentioned in the present invention do not exclude the existence of other method steps before and after the combination step or the insertion of other method steps between these explicitly mentioned steps; it should also be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to limit the scope of the present invention. The change or adjustment of the relative relationship thereof shall also be regarded as the scope of the present invention without substantially changing the technical content.
[0042] In order to better understand the above technical scheme, the exemplary embodiments of the present invention are described in more detail below. Although exemplary embodiments of the present invention are shown, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.
[0043] The present invention will be further described below in conjunction with the following examples.
[0044] Example 1
[0045] A high-strength PET polyester material, the preparation method comprises the following steps:
[0046] Step 1, preparing modified glass fiber:
[0047] (1) Take an open glass beaker, pour 75wt% ethanol aqueous solution into it, then add silane coupling agent KH-570, stir magnetically for 3 minutes at room temperature, and then weigh alkali-free glass fiber ( L: 5mm), and add it into a beaker so that the glass fiber is completely immersed in the solution. The mass volume ratio of the glass fiber, KH-570 and the ethanol solution is 1g: 0.3g: 10mL, and then the beaker is placed in an ultrasonic cleaning machine, and the ultrasound is turned on. It is treated at a frequency of 30kHz for 4h. After the treatment is completed, the liquid in the beaker is poured into a suction filtration funnel, and the liquid is removed by suction filtration. Then, anhydrous ethanol is continuously poured into it for cleaning for 15s, and then the glass fiber obtained by suction filtration is collected and dried in a vacuum drying oven to obtain a surface double-bonded glass fiber;
[0048] (2) Weigh hydroxyl-terminated polydimethylsiloxane (molecular weight of 1600, hydroxyl content of 2.5wt%), and weigh 4-mercaptobutyric acid and solvent chloroform, mix them into a reaction bottle, the mass volume ratio of hydroxyl-terminated polydimethylsiloxane, 4-mercaptobutyric acid and chloroform is 10g:6.6g:80mL, stir evenly at room temperature, then add 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC·HCl) and 4-dimethylaminopyridine (DMAP), the mass ratio of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride, 4-dimethylaminopyridine and hydroxyl-terminated polysiloxane is 2.9:0.8:10, under room temperature, magnetic stirring is carried out for 24h. After the reaction is completed, the solvent is removed under reduced pressure, and then washed three times with pure water and vacuum dried to obtain mercapto polysiloxane;
[0049] (3) Weigh the mercapto polysiloxane and the solvent chloroform and mix them into a reaction bottle, stir them mechanically until they are uniform, then slowly add the surface double-bonded glass fiber, the mass volume ratio of the surface double-bonded glass fiber, mercapto polysiloxane and chloroform is 1g:1.8g:15mL, then add the photoinitiator benzoin dimethyl ether, the addition amount is 0.9% of the mass of the mercapto polysiloxane, use a glass rod to stir and disperse them uniformly, and then mechanically stir them under ultraviolet light, the intensity of which is 325μW / cm 2 , irradiation wavelength 365nm, stirring time is 1.5h, stirring speed is 150r / min, after the reaction is completed, remove the UV lamp, pour the liquid in the reaction bottle into the suction funnel for vacuum filtration, remove the liquid, wash the fiber with ethanol three times, and dry it in a vacuum drying oven to obtain modified glass fiber. The microscopic morphology of the product is as follows Figure 1 shown.
[0050] Step 2, preparing PET polyester material:
[0051] PET resin (density 1.38g / cm 3 , melt index is 8g / 10min (190℃ / 2.16kg)), toughening agent (Arkema AX8900), antioxidant (antioxidant 1098) and modified glass fiber prepared in step 1 are weighed according to a mass ratio of 85:3:2:20, treated in an oven at 110℃ for 6h, and then the raw materials except the modified glass fiber are added to the mixer, the stirring speed is 150rpm, the stirring time is 15min, and after sufficient mixing, the raw materials are introduced into the started twin-screw extruder, and the modified glass fiber is added to the extruder through the side feeding port. After melt extrusion treatment, the melt extrusion temperature range includes: zone 1: 240℃, zone 2: 250℃, zone 3: 260℃, zone 4: 270℃, zone 5: 280℃, the screw speed is 100rpm, the aspect ratio L / D is 28:1, and after granulation, PET polyester material is obtained. The microscopic morphology of the product is as follows Figure 2 shown.
[0052] Example 2
[0053] A high-strength PET polyester material, the preparation method comprises the following steps:
[0054] Step 1, preparing modified glass fiber:
[0055] (1) Take an open glass beaker, pour 70wt% ethanol aqueous solution into it, then add silane coupling agent KH-570, stir magnetically for 2 minutes at room temperature, and then weigh alkali-free glass fiber ( L: 5mm), and add it into a beaker so that the glass fiber is completely immersed in the solution. The mass volume ratio of the glass fiber, KH-570 and the ethanol solution is 1g:0.2g:6mL, and then the beaker is placed in an ultrasonic cleaning machine, and the ultrasound is turned on. It is treated at a frequency of 25kHz for 2h. After the treatment is completed, the liquid in the beaker is poured into a suction filtration funnel, and the liquid is removed by suction filtration. Then, anhydrous ethanol is continuously poured into it for cleaning for 10s, and then the glass fiber obtained by suction filtration is collected and dried in a vacuum drying oven to obtain a surface double-bonded glass fiber;
[0056] (2) Take hydroxyl-terminated polydimethylsiloxane (molecular weight of 1000, hydroxyl content of 1.5wt%), 4-mercaptobutyric acid and solvent chloroform and mix them in a reaction bottle. The mass volume ratio of hydroxyl-terminated polydimethylsiloxane, 4-mercaptobutyric acid and chloroform is 10g:5.4g:50mL. Stir evenly at room temperature, then add 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC·HCl) and 4-dimethylaminopyridine (DMAP). The mass ratio of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride, 4-dimethylaminopyridine and hydroxyl-terminated polysiloxane is 2.1:0.6:10. Under room temperature conditions, magnetic stirring is carried out for 16 hours. After the reaction is completed, the solvent is removed under reduced pressure, and then washed three times with pure water and vacuum dried to obtain mercapto polysiloxane;
[0057] (3) The mercapto polysiloxane and the solvent chloroform are mixed into a reaction bottle, and stirred thoroughly until uniform. Then, the surface double-bonded glass fiber is slowly added. The mass volume ratio of the surface double-bonded glass fiber, the mercapto polysiloxane and the chloroform is 1 g:1.3 g:10 mL. Then, the photoinitiator benzoin diethyl ether is added. The amount added is 0.6% of the mass of the mercapto polysiloxane. A glass rod is used to stir and disperse the mixture uniformly. Then, the mixture is mechanically stirred under ultraviolet light. The intensity of the irradiation is 300 μW / cm 2, irradiation wavelength is 365nm, stirring time is 1h, stirring speed is 100r / min. After the reaction is completed, remove the UV lamp, pour the liquid in the reaction bottle into a suction funnel for vacuum filtration, remove the liquid, wash the fiber with ethanol three times, and dry it in a vacuum drying oven to obtain modified glass fiber.
[0058] Step 2, preparation of high-strength PET polyester material:
[0059] According to PET resin (density 1.38g / cm 3 , melt index is 8g / 10min (190℃ / 2.16kg)), toughening agent (Arkema E920), antioxidant (antioxidant 1330) and the mass ratio of the modified glass fiber prepared in step 1 is 80:2:1:10, each component is weighed separately, treated in an oven at 100℃ for 4h, and then PET resin, toughening agent and antioxidant are added to a mixer, the stirring speed is 100rpm, the stirring time is 10min, and after sufficient mixing, it is introduced into a twin-screw extruder, and the modified glass fiber is added to the extruder through the side feeding port at the same time, and melted, extruded and granulated. The extrusion temperature range includes: zone 1: 240℃, zone 2: 240℃, zone 3: 250℃, zone 4: 250℃, zone 5: 270℃, the screw speed is 50rpm, and the aspect ratio L / D is 25:1, and finally a high-strength PET polyester material is obtained.
[0060] Example 3
[0061] A high-strength PET polyester material, the preparation method comprises the following steps:
[0062] Step 1, preparing modified glass fiber:
[0063] (1) Take an open glass beaker, pour 80wt% ethanol aqueous solution into it, then add silane coupling agent KH-570, stir magnetically for 3 minutes at room temperature, and then weigh alkali-free glass fiber ( L: 5mm), and add it into a beaker so that the glass fiber is completely immersed in the solution. The mass volume ratio of the glass fiber, KH-570 and the ethanol solution is 1g:0.4g:12mL, and then the beaker is placed in an ultrasonic cleaning machine, and the ultrasound is turned on. It is treated at a frequency of 35kHz for 6h. After the treatment is completed, the liquid in the beaker is poured into a suction filtration funnel, and the liquid is removed by suction filtration. Then, anhydrous ethanol is continuously poured into it for cleaning for 20s, and then the glass fiber obtained by suction filtration is collected and dried in a vacuum drying oven to obtain a surface double-bonded glass fiber;
[0064] (2) hydroxyl-terminated polydimethylsiloxane (molecular weight of 2000, hydroxyl content of 3.5wt%), 4-mercaptobutyric acid and solvent chloroform were mixed into a reaction bottle, the mass volume ratio of hydroxyl-terminated polydimethylsiloxane, 4-mercaptobutyric acid and chloroform was 10g:7.2g:100mL, and stirred evenly at room temperature, and then 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC·HCl) and 4-dimethylaminopyridine (DMAP) were added, and the mass ratio of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride, 4-dimethylaminopyridine and hydroxyl-terminated polysiloxane was 3.6:1.2:10. Under room temperature conditions, magnetic stirring was performed for 32 hours. After the reaction was completed, the solvent was removed under reduced pressure, and then washed three times with pure water and vacuum dried to obtain mercapto polysiloxane;
[0065] (3) The mercapto polysiloxane and the solvent chloroform are mixed into a reaction bottle, and stirred thoroughly until uniform. Then, the surface double-bonded glass fiber is slowly added. The mass volume ratio of the surface double-bonded glass fiber, the mercapto polysiloxane and the chloroform is 1 g:2.6 g:20 mL. Then, the photoinitiator benzoin dimethyl ether or benzoin diethyl ether is added. The amount added is 1.2% of the mass of the mercapto polysiloxane. A glass rod is used to stir and disperse the mixture uniformly. Then, the mixture is mechanically stirred under ultraviolet light. The intensity of the irradiation is 350 μW / cm 2 , the irradiation wavelength is 365nm, the stirring time is 2h, the stirring speed is 200r / min. After the reaction is completed, the UV lamp is removed, the liquid in the reaction bottle is poured into a suction funnel for vacuum filtration to remove the liquid, the fiber is washed three times with ethanol, and then dried in a vacuum drying oven to obtain modified glass fiber.
[0066] Step 2, preparation of high-strength PET polyester material:
[0067] According to PET resin (density 1.38g / cm 3 , melt index is 8g / 10min (190℃ / 2.16kg)), toughening agent (Arkema AC1820), antioxidant (antioxidant 259) and modified glass fiber in a mass ratio of 90:5:3:30, weigh each component separately, treat in an oven at 120℃ for 8h, then add PET resin, toughening agent and antioxidant into a mixer, the stirring speed is 200rpm, the stirring time is 20min, after fully mixing, introduce into a twin-screw extruder, and at the same time, add the modified glass fiber into the extruder through the side feeding port for melting, extrusion and granulation. The extrusion temperature range includes: zone 1: 260℃, zone 2: 260℃, zone 3: 270℃, zone 4: 280℃, zone 5: 290℃, the screw speed is 150rpm, the aspect ratio L / D is 30:1, and finally a high-strength PET polyester material is obtained.
[0068] Comparative Example 1
[0069] A PET polyester material, which is different from Example 1 in that the glass fiber is not modified, and the polyester material is directly prepared by using the glass fiber and PET resin and other materials. Specifically, step 1 of Example 1 is omitted, and the modified glass fiber in step 2 is replaced by ordinary glass fiber, and the remaining steps and components are the same as Example 1.
[0070] Comparative Example 2
[0071] A PET polyester material, which differs from Example 1 in that the glass fiber is only subjected to surface silanization treatment to obtain surface double-bonded glass fiber, and the surface double-bonded glass fiber is directly used with materials such as PET resin to prepare the polyester material. Specifically, only step (1) of step 1 in Example 1 is retained, and the modified glass fiber in step 2 is replaced by the surface double-bonded glass fiber, and the remaining steps and components are the same as Example 1.
[0072] Comparative Example 3
[0073] A PET polyester material, which is different from Example 1 in that ordinary glass fiber is first mixed with hydroxyl-terminated polydimethylsiloxane, and then prepared into a polyester material with materials such as PET resin. Specifically, the modified glass fiber in step 2 is replaced by a mixture of glass fiber and hydroxyl-terminated polydimethylsiloxane, the mass ratio of glass fiber to hydroxyl-terminated polydimethylsiloxane is 1:1.8, and the remaining steps and ingredients are the same as Example 1.
[0074] Experimental testing
[0075] In order to more clearly illustrate the content of the present invention, the conventional strength and strength change performance under wet heat of the PET polyester materials prepared in Example 1 and Comparative Examples 1-3 were tested. The test items included: the test of tensile strength and elongation at break was referenced to GB / T 1040-2006, and the test of impact strength was referenced to GB / T 1043-2008. The results are shown in the following table:
[0076]
[0077] It can be seen from the above table that under normal temperature and humidity (25°C / 55%RH), compared with Comparative Examples 1-3, the PET polyester material prepared in Example 1 has a more obvious improvement in tensile strength and impact strength; and after 120h of wet heat treatment (65°C / 95%RH), the change rates of tensile strength and impact strength of Example 1 are much smaller than those of other comparative examples, indicating that it has better stability under wet heat conditions. In summary, it is shown that the PET polyester material prepared in Example 1 of the present invention not only has high strength, but also has good wet heat resistance, and can be used in a variety of complex environments, especially in wet heat environments.
[0078] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a high-strength PET polyester material, characterized in that: The following steps are involved: Step 1, preparing modified glass fiber: The glass fiber is treated with a silane coupling agent KH-570 to obtain a surface double-bonded glass fiber; and then the surface double-bonded glass fiber is subjected to a click chemical reaction with a mercapto-polysiloxane to prepare a modified glass fiber; Step 2, preparation of high-strength PET polyester material: After drying, PET resin, toughening agent and antioxidant are added into a mixer, fully mixed, and then introduced into a twin-screw extruder. Then, the modified glass fiber is added into the extruder through a side feed port. After melting, extrusion and granulation, a high-strength PET polyester material is obtained. In the step 2, the mass ratio of PET resin, toughening agent, antioxidant and modified glass fiber is 80-90:2-5:1-3:10-30.
2. The method for preparing a high-strength PET polyester material according to claim 1, characterized in that: In the step 1, the method for preparing the surface double-bonded glass fiber comprises: Firstly, the silane coupling agent KH-570 is dissolved in an ethanol solution, and then the glass fiber is added and ultrasonically treated. After the treatment, the glass fiber is filtered, washed and dried to prepare the surface double-bonded glass fiber.
3. The method for preparing a high-strength PET polyester material according to claim 2, characterized in that: In the preparation process of the surface double-bonded glass fiber, the mass fraction of the ethanol solution is 70%-80%, and the mass volume ratio of the glass fiber, the silane coupling agent and the ethanol solution is 1g: (0.2-0.4)g: (6-12)mL.
4. The method for preparing a high-strength PET polyester material according to claim 1, characterized in that: In the step 1, the preparation method of mercapto polysiloxane comprises: Take terminal hydroxyl polysiloxane, 4-mercaptobutyric acid and solvent chloroform, mix them, add 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 4-dimethylaminopyridine after stirring evenly, and stir them magnetically at room temperature for 16-32 hours. After the reaction is completed, remove the solvent under reduced pressure, and then wash and dry to obtain mercapto polysiloxane.
5. The method for preparing a high-strength PET polyester material according to claim 4, characterized in that: In the preparation process of the mercapto polysiloxane, the mass volume ratio of the terminal hydroxyl polysiloxane, 4-mercaptobutyric acid and chloroform is 10g:(5.4-7.2)g:(50-100)mL.
6. The method for preparing a high-strength PET polyester material according to claim 4, characterized in that: In the preparation process of the mercapto polysiloxane, the mass ratio of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 4-dimethylaminopyridine and hydroxyl-terminated polysiloxane is 2.1-3.6:0.6-1.2:
10.
7. The method for preparing a high-strength PET polyester material according to claim 1, characterized in that: In step 1, the preparation method of the click chemistry reaction includes: The mercapto polysiloxane and chloroform are mixed and stirred until uniform, and the surface double-bonded glass fiber and the photoinitiator are added, and then stirred under ultraviolet light. After the reaction is completed, the liquid is removed by suction, and the modified glass fiber is obtained after washing and drying.
8. The method for preparing a high-strength PET polyester material according to claim 7, characterized in that: During the click chemistry reaction, the mass volume ratio of the surface double-bonded glass fiber, the mercapto-polysiloxane and the chloroform is 1 g:(1.3-2.6) g:(10-20) mL.
9. The method for preparing a high-strength PET polyester material according to claim 1, characterized in that: In step 2, the toughening agent is one or more combinations of Arkema AX8900, Arkema E920, and Arkema AC1820; the antioxidant is one or more combinations of antioxidant 1098, antioxidant 1330, antioxidant 1790, and antioxidant 259.
10. A high-strength PET polyester material, characterized in that: The high-strength PET polyester material is prepared by the preparation method described in claim 1.
Citation Information
Cited By
Food-grade beverage bottle material and preparation method thereof
CN122037496A